2021
DOI: 10.20944/preprints202102.0423.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of the Relationship between Executive Functions and Intelligence in Gifted Student: A Pilot Study.

Abstract: (1) Background: Executive functioning is a concept that suggests a scheme of relationship between brain-mind and behavior, through a plan and control of individuals actions on tasks and context. This work is an approach to the study between relationship of abilities (flair) and the execution, between cognitive development and executive functioning as intelligence and creativity and reading writing learning association. The objective is trying to give a definition of neuropsychological profile of Gifted Student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results showed that gifted students performed better in verbal and visual working memory. Moreover, Rojas et al (2021) analyzed the relationship between EF and intelligence in gifted student. They studied 20 gifted students assessments by a school counselor.…”
Section: Conceptual Approach Of Efmentioning
confidence: 99%
“…The results showed that gifted students performed better in verbal and visual working memory. Moreover, Rojas et al (2021) analyzed the relationship between EF and intelligence in gifted student. They studied 20 gifted students assessments by a school counselor.…”
Section: Conceptual Approach Of Efmentioning
confidence: 99%